(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Laboratory physicians confront with ethical issues in routine practice, but still ethics does not draw the importance it deserves. A critical appraisal of the existing postgraduate curriculum of Pathology, Microbiology and Biochemistry with reference to its Bioethical inclusions to their conformity with reference to Bioethical principles applicable to profession as included in UNESCO Declaration is needed. Aim: To critically analyse the inclusions of “Bioethics in Laboratory Medicine” into the Existing Postgraduate Curriculum of Pathology, Microbiology and Biochemistry with reference to Bioethical principles incorporated in UNESCO Declaration Material and Methods: It was a descriptive study for rapid review of literature for the purposes of identification and critical appraisal of bioethical considerations in Laboratory Medicine in existing Guidelines for Competency Based Postgraduate Training Programme for MD in Pathology, Microbiology, Biochemistry with reference to Bioethical principles included in UNESCO declaration specially those applicable to profession and not propagation or advocacy. Observations and Results: Upon critical analysis and mapping of the competencies in the Guidelines for Competency Based Postgraduate Training Programme for MD in Pathology, Microbiology, Biochemistry with the principles in the UNESCO universal declaration, 16 competencies were identified as professional ethical inclusions. 19 Competencies suggested in regards to “Bioethics in Laboratory Medicine” for Guidelines for Competency Based Postgraduate Training Programme for MD In these subjects to make them commensurate with UNESCO universal declaration Conclusion: This has brought out subsequent omissions which need to be managed in order to make competencies in Existing PG curriculum of Pathology, Microbiology and Biochemistry comparable with the UNESCO universal declaration and therefore, make it better and standardised on global and international level.